A revolta dos dândis : a elite da advocacia pública sergipana, profissionalismo e poder - Lima, Aline Magna Cardoso Barroso (2016)
This work analyzes the patterns of recruitment and selection of the lawyers publics elite in the Brazilian State of Sergipe. Focusing initially on the relations between the legal and political space in the institutionalization process the state attorney career in Sergipe, in intenden to comprehend the historical and social conditions of formation that rulling elite. Recently, the state attorney started the discussion the importance their profession, with the resolute purpose in motion the process of professional career, passing by the implementation of the ideology of professionalism and meritocracy imported from core countries. Conflicts arising there from confined in the context of the need for border demarcation between the professional and the political in a country that historically guided the access and mobility in the legal profession by the logic of personal relationships. From the investigation into high positions occupation rules on prosecutors of space, the intention of the work, to discuss issues surrounding the problem of professionalization of the State Attorney careers, is to examine the form of production of discourses and toggle positions within the group to face the questioning of social practices, concepts and meanings into play in the interaction of these singularly considered individuals and groups that have formed within the common social space. The composition´s examination of the ruling elite the institution, in different historical periods, and recent divisions of the group revealed that the effects of social and demographic diversification of the group, from the 1990s, became progressively mobile conflicts in inside the field that, despite this, it kept the old logic of recruitment and selection its ruling elite, primarily recruited from the remarkable origins holders, endowed with social capital and political relationship needed to win the game.